(untitled) (Journal of Creative Industry and Sustainable Culture, 2022)
During the global pandemic, we now live and work differently, forcing government decision-makers to find innovative, new ways to learn and train that will still be feasible during the pandemic. As we move slowly away from the Covid-19 shadow, upskilling and reskilling students are crucial for learning and professional development. Consequently, the pandemic has highlighted the necessity for transforming distance learning and opened new opportunities for immersive virtual exchanges. Nowadays, virtual reality (VR) has a significant role in fighting the Covid-19 pandemic. This paper proposes the potential of integrating VR technology in learning and training perspectives as an effective strategy or approach used to complete students experiences. The purpose of this study is to develop and design a virtual environment (VE) that guides students through the educational process at high levels of performance. The focus of this study was to evaluate the effectiveness of a VR simulation for students. In this study, we have designed a VR simulation using Unity 3D software connected with the Hp reverb G2 headset. We collected data by a survey which indicates 50 samples attending a soft skills training course. The results revealed that virtual learning (V-learning) in VR is much more interactive and effective than traditional learning methods like E-learning and classrooms. This study contributes a significant role that the adoption of VR technology can be extremely beneficial to educators in helping students enhance their skills and continue the educational process in universities.